Employing the Theory of Planned Behavior to Predict Social Media Use Behavior - Ghufron, M Nur; Nasir, Amin (Program Studi Pendidikan Agama Islam, 2022)
This study aims to determine whether the designed model fits the empirical model and whether attitudes toward social media use, subjective norms, self-efficacy, and intentions to use social media are factors in the social media use behavior in Madrasah Tsanawiyah students. The population in this study was all Madrasah Tsanawiyah students in Central Java. The sampling technique in this study was systematic sampling. It was conducted by taking each subject in the population until the number of the desired sample was met. The technique of analysis employed the structural equation model. Based on the analysis results, the requirements criteria were Chi-Square 165.472 (DF= 81, p=0.000), CMIN/DF=2.043, GFI= 0.947, AGFI= 0.922, TLI= 0.940, and RMSEA= 0.051. Then, the proposed model could be said to be fit or fulfilled. Thus, it can be stated that the proposed model design was not significantly different from the empirical data. Under the study results, the determination coefficient (R²) of the social media use intention (R²) was 0.03, meaning that only 3% could be explained or predicted through the variables of attitude toward using social media, subjective norms, and self-efficacy. In addition, the coefficient of determination (R²) of social media use behavior was 0.29, indicating that 29% could be explained or predicted through the variables of social media use attitudes, subjective norms, self-efficacy, and intentions.